Symptoms into words: how medical patients talk about fatigue - Standen, Penny; Ward, Christopher D.; Saunders, Laura; Beer, Charlotte (Palgrave Macmillan, 2015)
Fatigue, which is the central symptom of CFS/ME, is notoriously difficult to define. We describe an investigation in which we raise two questions. First, does the way people use fatigue-related language reflect distinctive patterns? Second, is there a particular pattern characteristic of CFS/ME? These questions can be asked with various theories of language and meaning in mind, as we discuss. Our orientation is towards the intersubjective realities revealed by language, rather than towards the neurological substrate of fatigue. We created a questionnaire including 105 items connected with the experience of fatigue. We then compared responses in samples of adults fulfilling clinical criteria for three conditions in which fatigue is described: CFS/ME, Parkinson ’s disease, and multiple sclerosis. Principal components factor analysis of the three groups together did suggest patterns that we think reflect different intersubjective realities connected with fatigue-related language. In the CFS/ME group, cluster analysis showed that the pattern of responses differed significantly from the other two diagnostic groups. Cluster analysis does not reveal the nature of differences but the CFS/ME respondents marked a higher number of questionnaire items as ‘exactly how I feel ’. We suggest that the language used by people diagnosed with CFS/ME represents less localised experiences than in the other two diagnoses. In the interpretation of symptoms it is helpful to make a distinction between a generalised feeling and an experience that is more readily localised in time and space.